Mobile operator strategies to reach low-income communities in South Africa - Arendse, Brian David (My University, 2014)
The purpose of this research is to identify specific strategies adopted by mobile telecommunications operators in South Africa to reach low income communities in a profitable and sustainable manner. The first sub-problem is to identify specific strategies adopted by mobile telecommunications operators in South Africa. The second sub-problem is to justify the appropriateness of specific strategies adopted by mobile telecommunications operators in South Africa to reach low income communities in a profitable and sustainable manner. Mobile Operator Strategy in South Africa has focused on subscriber acquisition, growing and maintaining market share, revenue growth and operational efficiency. End-user success factors focusing on innovative end-user services have been the biggest factors enabling financial success for Mobile Network Operators (MNOs) in South Africa. Supporting success factors for example regulatory compliance and corporate social responsibility have played a role in supporting the financial success factors for South African MNOs. The research includes a study of the Mobile Operators strategy up to present and considers alternative MNO strategies, considering future industry developments including future new revenue streams like M-Commerce and Media and threat of substitutes in the form of over-the-top players. Key findings in this research are that both MNOs studied have proved to have similar strategies to reach low-income communities, focussing on innovative end-user offerings that generate revenues. Future developments in the telecommunications industry where over-the-top service providers like Google, Facebook and Apple are emerging will need operators to rethink their approach to the market in order to maintain the potential industry revenue growth.
Keywords: Mobile communication systems -- South Africa. Telecommunication -- South Africa.Cell phone services industry -- South Africa.